Preparation method of composite substrate for semiconductor device production
By adopting the composite substrate preparation method in semiconductor substrate materials, high-temperature sintering and pulsed electric field deposition processes of carbon substrates and tantalum carbides, the performance reduction of the substrate materials in high temperature and corrosion environments is solved, and higher electrical conductivity and thermal conductivity are achieved, ensuring the stability of semiconductor devices in extreme environments.
Patent Information
- Application Number
- CN202510182027.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-19
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-02-19
AI Technical Summary
Semiconductor substrate materials are prone to crystalline changes or lattice distortion at high temperatures, resulting in the atomic arrangement losing its ideal orientation and being easily oxidized or eroded in a corrosive environment, affecting the uniform arrangement of crystalline directions, and thus reducing the electrical and thermal conductivity of the substrate materials.
Using a method of preparing a composite substrate, a carbon substrate is heated to 1000~1500°C in a hydrogen atmosphere, and then a pulsed electric field assisted vapor deposition is performed in a reaction chamber with a pulsed electric field to form a crystal-oriented tantalum carbide precoated material, and high-temperature sintering is performed in a high-temperature sintering furnace to obtain a dense composite substrate.
Through the orientation arrangement of the crystal direction, the tantalum carbide coating achieves higher electrical conductivity and thermal conductivity in specific directions, helping semiconductor devices to quickly dissipate heat in high-power and high-temperature environments, ensuring stable performance, and improving the density, strength and stability of the coating.
Smart Images

Figure CN119833393A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of semiconductor device production, and in particular relates to a method for preparing a composite substrate for semiconductor device production. Background Art
[0002] Semiconductor substrate is a material foundation for building semiconductor devices. It provides physical support for semiconductor devices and acts as a basic layer for electrical performance in the device. In semiconductor manufacturing, the substrate is usually the first material layer processed, and other semiconductor structures and electronic components are built on its surface through multi-layer deposition and doping. The semiconductor substrate is a key component of the entire device and has an important impact on device performance.
[0003] The degree of lattice matching between semiconductor materials and substrate materials will affect the crystal quality and stress distribution of the deposited layer, and affect the performance and reliability of the device. Commonly used semiconductor substrate materials include silicon, gallium arsenide, gallium nitride, silicon carbide, sapphire, etc. However, on the one hand, the semiconductor substrate material will undergo crystal orientation changes or lattice distortion at high temperatures, causing the atomic arrangement to lose its ideal orientation. On the other hand, the preparation process of semiconductor devices needs to be in a highly corrosive environment. Conventional semiconductor materials are easily oxidized or corroded, and surface damage will affect the uniform arrangement of crystal directions. The directional arrangement of the crystal directions is destroyed, thereby reducing the electrical conductivity and thermal conductivity of the substrate material. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a method for preparing a composite substrate for semiconductor device production, aiming to solve the problem that the crystal orientation is difficult to be oriented and the electrical conductivity and thermal conductivity of the substrate material are reduced.
[0005] To solve the above technical problems, the present invention is implemented as follows: a method for preparing a composite substrate for producing a semiconductor device, the steps comprising: S1. Place the raw carbon into a reaction chamber in a hydrogen atmosphere, evacuate the reaction chamber, heat it to 1000-1500°C, keep it warm for 1-3 hours, and cool and clean it to obtain a carbon substrate; S2, grinding and mixing the tantalum source, tantalum fluoride and flux to obtain coating powder; S3, transferring the coating powder to a reaction chamber with a pulsed electric field, performing pulsed electric field assisted vapor deposition, and obtaining a tantalum carbide pre-coating material with crystal orientation after cooling; S4. Transfer the tantalum carbide pre-coating material to a high-temperature sintering furnace, and heat it at 1800-2400° C. in an inert atmosphere for 0.5-6 hours to obtain a composite substrate, which is used for semiconductor device production.
[0006] In some embodiments of the present invention, in step S2, the flux includes at least one of sodium fluoride, potassium fluoride, calcium fluoride, sodium chloride, potassium carbonate, sodium carbonate, sodium metaborate, sodium borate, magnesium chloride, calcium chloride, lithium chloride, calcium oxide, and magnesium oxide; The tantalum source includes at least one of tantalum alkane, tantalum vinyl compound, tantalum acetate, and tantalum olefinic compound.
[0007] In some embodiments of the present invention, calculated by weight percentage, the tantalum source accounts for 60-80 wt%, the tantalum fluoride accounts for 10-20 wt%, and the flux accounts for 10-20 wt%.
[0008] In some embodiments of the present invention, step S3 includes: S3.1, transferring the coating powder into a reaction chamber with a pulsed electric field and placing the carbon substrate on the interface of the coating powder; S3.2, introducing an inert atmosphere into the reaction chamber and applying a pulsed electric field to perform a first deposition to obtain a preliminary deposition substrate, wherein the deposition temperature of the first deposition is ; S3.3, introducing hydrogen atmosphere into the reaction chamber and adjusting the pulse electric field, performing a first annealing treatment on the preliminary coating substrate to obtain a preliminary coating substrate, wherein the first annealing temperature is ; S3.4, performing an nth deposition and an nth annealing on the preliminary coating substrate to obtain a tantalum carbide pre-coating material, wherein the nth deposition temperature is , the nth annealing temperature is .
[0009] In some embodiments of the present invention, the is 800~1000℃, for Said is the rate of change of deposition temperature, is 100~300℃, for , is the rate of change of annealing temperature, It is 200~400℃.
[0010] In some embodiments of the present invention, in step S3.3, the formula for adjusting the pulse electric field is: , where t is the upper limit of the integral, indicating the total duration of the annealing process, is the variable in the integration process, representing the time point from the start of annealing to a certain moment, E(t) is the relationship between the pulse electric field intensity and time during the annealing process, is the proportionality coefficient between the temperature increment and the electric field strength, indicating the incremental effect of the electric field strength on the annealing temperature. is the rate at which the pulse electric field affects the temperature, It is the feedback coefficient of the attenuation of the pulse electric field effect during the temperature and annealing process.
[0011] In some embodiments of the present invention, ,in, is the initial electric field strength, is the attenuation coefficient, which represents the rate at which the pulse electric field intensity decays with time.
[0012] In some embodiments of the present invention, step S3.4 includes: Performing an nth deposition and an nth annealing on the preliminary coating substrate; Determining whether the exhaust gas content of the reaction chamber is within a preset gas content range, wherein the preset gas content range is calculated based on the amount of the coating powder and the chemical reaction; If yes, then stop the next deposition and proceed to step S4; If not, the steps of performing the nth deposition and nth annealing on the preliminary coating substrate are performed.
[0013] In some embodiments of the present invention, the exhaust gas of the reaction chamber includes at least one of hydrogen chloride, hydrogen fluoride, water vapor, carbon monoxide, and carbon dioxide.
[0014] Compared with the prior art, the method for preparing the composite substrate for semiconductor device production in the present invention has the following beneficial effects: The high melting point and chemical stability of tantalum carbide, combined with the high-temperature sintering and hydrogen atmosphere treatment process of the present invention, enable the coating to maintain physical and chemical stability under high temperature conditions and will not easily decompose or deform. On the composite substrate, electrical conductivity and thermal conductivity are important requirements. Through the directional arrangement of crystal directions, the tantalum carbide coating achieves higher electrical conductivity and thermal conductivity in a specific direction, which helps semiconductor devices to quickly dissipate heat in high-power, high-temperature environments and ensure stable performance. The specific crystal orientation arrangement also improves the density, strength, stability of the coating and its bonding with the carbon substrate, ensuring the stability of the composite substrate in extreme environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 It is a schematic flow chart of a method for preparing a composite substrate for producing semiconductor devices in one embodiment of the present invention. DETAILED DESCRIPTION
[0016] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0017] Please refer to Figure 1 The present invention provides a method for preparing a composite substrate for producing a semiconductor device, the steps comprising: S1. Place the raw carbon into a reaction chamber with a hydrogen atmosphere, evacuate the reaction chamber, raise the temperature to 1000-1500°C, for example, 1000°C, 1200°C, 1500°C, keep the temperature for 1-3h, for example, 1h, 2h, 3h, cool and clean to obtain a carbon substrate.
[0018] The carbon raw material is heated to 1000~1500℃ in a hydrogen atmosphere and maintained for 1~3 hours to ensure the purity and structural stability of the carbon substrate. The hydrogen atmosphere helps to remove surface impurities, prevent oxidation, and make the surface of the carbon substrate purer and smoother, providing an ideal foundation for the subsequent tantalum carbide deposition, forming a high-purity, structurally stable carbon substrate, providing a better bonding interface, and improving the adhesion and stability of the tantalum carbide coating.
[0019] The specific structure and ventilation method of the reaction chamber are known to those skilled in the art and will not be described in detail here.
[0020] S2. Grind and mix the tantalum source, tantalum fluoride and flux to obtain a coating powder. By grinding and uniformly mixing the tantalum source, tantalum fluoride and flux, a coating powder suitable for vapor deposition is obtained. The uniformity and fine particle size of the powder ensure that tantalum carbide can be uniformly deposited on the carbon substrate during the deposition process. The reactivity of the tantalum element during the deposition process is improved, ensuring the uniformity and flatness of the coating, and the role of the flux helps to achieve tantalum deposition at a lower temperature.
[0021] S3. Transfer the coating powder to a reaction chamber with a pulsed electric field, perform pulsed electric field assisted vapor deposition, and obtain a tantalum carbide pre-coating material with crystal orientation after cooling. Carry out vapor deposition in a reaction chamber with a pulsed electric field, and use the action of the pulsed electric field to control the growth direction of the tantalum carbide crystals to form directional tantalum carbide crystals. This process enhances the compactness and orientation of the coating, aligns the crystals in a specific direction, and improves the electrical conductivity and thermal conductivity of the material. A tantalum carbide pre-coating with crystal orientation is obtained, and the crystal orientation can be (100) or (111) crystal orientation, ensuring that the electrical and thermal properties of the coating in a specific direction are better, and enhancing the coating's ability to resist peeling. The pulsed electric field application device is known to those skilled in the art and will not be described in detail here.
[0022] Crystal orientation refers to the arrangement of atoms in a certain direction in a crystal. Crystal orientation can be represented by Miller indices, which identify the characteristics of atomic arrangement in different directions of the crystal. Miller indices are used to represent the direction of the crystal plane and the density of atomic arrangement. Different Miller indices represent different planes and directions in the crystal. For example, (100) and (111) crystal orientations refer to different crystal plane arrangements. The (100) crystal orientation represents a plane direction parallel to the edge of the basic unit of the lattice, and the (111) crystal orientation represents a direction that passes through the diagonal of the crystal. In many crystal structures, it is a relatively dense atomic arrangement direction.
[0023] The (100) crystal orientation usually has better electron migration characteristics, and the Young's modulus in the (100) direction is lower, showing better ductility and toughness. The (111) crystal orientation is a denser arrangement direction, with the most dense atomic arrangement. Due to the dense atomic arrangement, the thermal conductivity and electrical conductivity of the material in the (111) direction are usually higher, which is conducive to the effective conduction of heat and current. The crystal structure in the (111) direction is relatively strong, with high wear resistance and hardness, so it is very useful in situations where high strength is required.
[0024] S4. Transfer the tantalum carbide pre-coating material to a high-temperature sintering furnace, and heat it at 1800-2400°C in an inert atmosphere, for example, 1800°C, 2000°C, 2400°C, for 0.5-6h, for example, 0.5h, 3h, 6h, to obtain a composite substrate for use in semiconductor device production.
[0025] High temperature sintering in an inert atmosphere at 1800~2400℃ further enhances the compactness and structural stability of the tantalum carbide coating. High temperature sintering causes the particles in the coating to recrystallize, thereby improving the mechanical strength and wear resistance of the coating. The resulting dense tantalum carbide coated carbon material has higher bonding strength and oxidation resistance, and is suitable for the high temperature working environment of semiconductor materials.
[0026] The high melting point and chemical stability of tantalum carbide, combined with the high temperature sintering and hydrogen atmosphere treatment process of the present invention, enable the coating to maintain physical and chemical stability under high temperature conditions and will not easily decompose or deform. Electrical conductivity and thermal conductivity are important requirements on composite substrates. Through the directional arrangement of crystal directions, the tantalum carbide coating achieves higher electrical conductivity and thermal conductivity in a specific direction, which helps semiconductor devices to quickly dissipate heat in high-power, high-temperature environments and ensure stable performance.
[0027] The oxidation resistance of tantalum carbide coating can protect the composite substrate from oxidation damage under high temperature conditions, prolong the service life of the material, and improve the reliability of the equipment. The specific crystal orientation improves the density, strength and stability of the coating. This directional arrangement not only enhances the electrical and thermal properties, but also improves the bonding strength with the carbon substrate, ensuring the stability of the composite substrate in extreme environments.
[0028] Specifically, in step S2, the flux includes at least one of sodium fluoride, potassium fluoride, calcium fluoride, sodium chloride, potassium carbonate, sodium carbonate, sodium metaborate, sodium borate, magnesium chloride, calcium chloride, lithium chloride, calcium oxide, and magnesium oxide; the tantalum source includes at least one of tantalum alkane, tantalum vinyl compound, tantalum acetate, and tantalum olefin compound; and the tantalum fluoride includes at least one of tantalum pentafluoride, tantalum trifluoride, tantalum tetrafluoride, tantalum fluorochloride, and tantalum fluoride complex.
[0029] In one embodiment of the present invention, step S1 includes: S1.1. Select raw carbon as the substrate.
[0030] The raw carbon can be graphite, activated carbon, glassy carbon, etc. The choice of material depends on the application requirements of the final tantalum carbide coating. The carbon substrate will serve as a supporting material in subsequent processes, so the cleanliness and structural uniformity of its surface directly affect the quality of the coating.
[0031] S1.2. Place the raw carbon into the reaction chamber.
[0032] The reaction chamber should have good sealing and high temperature tolerance, and be equipped with a temperature control system and a vacuum system capable of controlling the atmosphere, pressure and temperature.
[0033] S1.3. Introduce high-purity hydrogen into the reaction chamber to form a hydrogen atmosphere.
[0034] The role of hydrogen is to remove oxides and impurities on the carbon surface and improve the purity of the carbon substrate. The hydrogen flow rate should be controlled within a certain range to ensure the formation of a stable reducing atmosphere in the reaction chamber to prevent oxidation of the carbon substrate surface.
[0035] S1.4. Evacuate the reaction chamber and start heating the reaction chamber under hydrogen atmosphere and vacuum conditions.
[0036] It is usually carried out at a lower pressure to remove air and impurity gases in the reaction chamber. Vacuum conditions help reduce the concentration of oxygen, further reducing the possibility of oxidation on the surface of the carbon substrate, while providing a pure atmosphere for the heating process. The choice of different temperatures affects the microstructure and surface activity of the carbon substrate. 1000°C is a relatively low temperature, which helps to remove surface impurities, but has little effect on the structure of the carbon substrate. It is suitable for processing relatively stable carbon substrate materials. 1200°C is a medium temperature, which can further activate the surface of the carbon substrate and enhance its bonding with subsequent coatings. 1500°C is a higher temperature, which helps to completely remove impurities and improve the crystallinity of the carbon substrate, making its surface smoother.
[0037] S1.5. When the temperature reaches the set value (e.g., 1000°C, 1200°C, or 1500°C), maintain the constant temperature for 1 to 3 hours, such as 1 hour, 2 hours, or 3 hours. After the insulation is completed, gradually reduce the temperature of the reaction chamber to cool the carbon substrate to room temperature.
[0038] The choice of holding time affects the purity and surface state of the carbon substrate. 1 hour is suitable for treating carbon substrates with lower processing requirements and for removing volatile impurities on the surface. 2 hours is suitable for further activating the surface of the carbon substrate, making it more suitable for subsequent coating adhesion. 3 hours is used for treating carbon substrates that require high purity, so that impurities are completely removed and the surface structure is more uniform and stable.
[0039] The cooling rate is generally controlled to be slow to avoid stress deformation or microstructural changes in the carbon substrate due to the sudden drop in temperature. The cooling process in a hydrogen atmosphere further protects the carbon substrate and prevents oxidation during the cooling process.
[0040] S1.6. Take out the cooled carbon substrate from the reaction chamber and clean the surface to remove any remaining surface deposits or impurities.
[0041] The cleaning process may include simple air blast cleaning, ultrasonic cleaning or solvent cleaning to ensure that the carbon substrate surface is completely clean and free of contamination.
[0042] In one embodiment of the present invention, in step S2, the tantalum source, tantalum fluoride and flux after preliminary grinding are mixed together in a certain proportion. In the mixed grinding stage, a ball milling method can be used to evenly mix powders of different components by putting the powders and ball milling media (such as zirconium oxide balls) into a grinder. The grinding time is usually 1 to 3 hours, for example, it can be 1 hour, 2 hours, 3 hours, to ensure that the different components are evenly distributed and the particle size and shape are similar. Mixing while grinding helps to ensure uniform evaporation and deposition of tantalum and fluorine elements in the subsequent deposition process to avoid material segregation.
[0043] Tantalum source accounts for 60~80 wt%, for example, it can be 60wt%, 70wt%, 80wt%. Tantalum source is the main material of tantalum carbide coating, and the proportion is high to ensure that the coating contains enough tantalum elements to form a dense tantalum carbide layer. The content of tantalum source is usually controlled at 60~80 wt%, which can be adjusted according to the required coating thickness and deposition rate.
[0044] The fluoride of tantalum accounts for 10-20 wt%, for example, it can be 10wt%, 15wt%, 20wt%. The fluoride of tantalum is a key component for providing tantalum and fluorine elements, and has the function of promoting the reactivity and dispersibility of tantalum during the deposition process. The proportion of tantalum fluoride is controlled at 10-20 wt%, which can enhance the uniformity of deposition and promote the reaction. Too high a proportion may lead to faster consumption of tantalum source, but too low a proportion may affect the deposition efficiency of tantalum.
[0045] The flux accounts for 10~20 wt%, for example, it can be 10wt%, 15wt%, 20wt%. The role of the flux is to reduce the reaction temperature, improve the fluidity and reactivity of the powder, especially to accelerate the deposition of tantalum in a low temperature environment. Too low a flux content may not effectively promote the reaction, while too high a content may introduce impurities during the deposition process or reduce the density of the coating.
[0046] In one embodiment of the present invention, step S3 includes: S3.1. The coating powder is transferred into a reaction chamber with a pulsed electric field and the carbon substrate is placed on the interface of the coating powder.
[0047] Ensure that the coating powder is in close contact with the carbon substrate, providing appropriate spatial structure and reaction conditions for the subsequent pulsed electric field deposition process. This operation helps to ensure that the powder is evenly dispersed under the action of the pulsed electric field, and can be efficiently and evenly deposited on the surface of the carbon substrate to form a preliminary coating.
[0048] S3.2, introducing an inert atmosphere into the reaction chamber and applying a pulsed electric field to perform a first deposition to obtain a preliminary deposition substrate, wherein the deposition temperature of the first deposition is .
[0049] Inert gas provides a non-oxidizing environment to prevent oxidation of the carbon substrate and coating powder during the deposition process, thereby improving the deposition quality. The pulsed electric field assisted deposition process achieves directional deposition of the powder on the substrate surface through the force of the electric field on the powder particles, thereby improving the density of the deposited layer. The first deposition can form a preliminary coating on the carbon substrate surface, providing a basis for subsequent multiple depositions. This process initially achieves the crystal orientation of the coating, enhancing the conductivity and heat resistance of the material.
[0050] S3.3, introducing hydrogen atmosphere into the reaction chamber and adjusting the pulse electric field, performing a first annealing treatment on the preliminary coating substrate to obtain a preliminary coating substrate, wherein the first annealing temperature is .
[0051] Annealing can eliminate the internal stress that may be generated during the first deposition process and improve the uniformity and density of the coating structure. By adjusting the pulsed electric field during the annealing process, the crystal growth direction can be further controlled, the crystal orientation of the coating can be optimized, and a higher structural stability can be achieved. After the first annealing, the crystal orientation of the coating substrate is more obvious and the structure is more stable, laying a good foundation for subsequent multiple depositions, while further enhancing the mechanical strength and thermal stability of the coating.
[0052] S3.4, performing n-th deposition and n-th annealing on the preliminary coating substrate to obtain a tantalum carbide pre-coating material, wherein the n-th deposition temperature is , the nth annealing temperature is . Multiple deposition and annealing cycles can increase the thickness and density of the coating, and gradually improve the crystal structure in each deposition and annealing. Through multiple deposition and annealing, the crystal orientation of the coating is further strengthened, so that the density and heat resistance of the tantalum carbide coating are significantly improved. The final tantalum carbide pre-coating material has excellent oxidation resistance, electrical conductivity and thermal conductivity, meeting the needs of high-performance applications.
[0053] in, The temperature is 800-1000°C, for example, 800°C, 900°C, 1000°C, for is the rate of change of deposition temperature, The temperature is 100-300°C, for example, 100°C, 200°C, 300°C. for , is the rate of change of annealing temperature, The temperature is 200-400°C, for example, 200°C, 300°C, or 400°C.
[0054] In step S3.3, the formula for adjusting the pulse electric field is: , where t is the upper limit of the integral, indicating the total duration of the annealing process, is the variable in the integration process, representing the time point from the start of annealing to a certain moment, E(t) is the relationship between the pulse electric field intensity and time during the annealing process, is the proportionality coefficient between the temperature increment and the electric field strength, indicating the incremental effect of the electric field strength on the annealing temperature. is the rate at which the pulse electric field affects the temperature, It is the feedback coefficient of the attenuation of the pulse electric field effect during the temperature and annealing process.
[0055] In this formula, the change of annealing temperature will affect the regulation of electric field strength. The purpose is to control the smooth change of temperature by reducing the electric field strength during the annealing process to avoid stress or structural instability in the material due to sudden temperature changes. It can be understood that as the annealing temperature rises, the electric field strength needs to be gradually reduced to ensure a stable temperature rise.
[0056] During the annealing process, as the temperature As the temperature rises, the electric field strength E(t) gradually decreases. This is to avoid structural instability or material stress caused by a too rapid temperature rise and to ensure that the temperature increases at an appropriate rate. The electric field strength E(t) will gradually decay with temperature (by Control), that is, when the temperature is low, the electric field strength is high to accelerate the initial temperature rise; when the temperature gradually approaches the target annealing temperature, the electric field strength gradually decreases to control the rate of temperature rise and avoid temperature overshoot.
[0057] In the early stage of annealing, the annealing temperature When the electric field strength E(t) is low, the temperature rises rapidly. This can be explained by the formula With the annealing temperature As the temperature gradually increases, the electric field strength E(t) begins to decrease, controlling the rate of temperature increase. At this point, the exponential decay term The electric field strength E(t) becomes significant, gradually weakening the incremental effect of the electric field strength on the temperature. When the annealing temperature approaches the set target temperature, the electric field strength E(t) has been significantly reduced, achieving the effect of temperature control, avoiding drastic temperature changes, and allowing the temperature to reach the target value steadily.
[0058] The β proportionality coefficient controls the incremental effect of the electric field strength on the temperature, and is between 0.1 and 1, for example, it can be 0.1, 0.5, and 1. A higher β value means that the electric field strength has a greater effect on the temperature, which is suitable for use during rapid initial temperature rise. The λ parameter controls the decay rate of the electric field strength to the temperature, and is between 0.01 and 0.5, for example, it can be 0.01, 0.3, and 0.5. A larger λ value causes the effect of the electric field strength to decay faster, thereby further weakening the effect of the electric field strength when approaching the target temperature. The γ temperature feedback coefficient can be between 0.01 and 0.1, for example, it can be 0.01, 0.05, and 0.1, and is used to adjust the feedback effect of temperature on the electric field strength to ensure the smoothness of temperature control.
[0059] In one embodiment of the present invention, ,in, is the initial electric field strength, is the attenuation coefficient, which represents the rate at which the pulse electric field intensity decays with time. It is 30000~50000 V / m, for example, it can be 30000V / m, 40000V / m, 50000V / .
[0060] During the annealing process, the electric field strength will gradually decay over time, avoiding the dramatic temperature rise caused by the initial high-intensity electric field, making the temperature rise more stable and uniform. By adjusting the decay rate α, α is 0.01~0.1, for example, it can be 0.01, 0.05, 0.1, the decay rate of the electric field strength can be controlled, thereby affecting the temperature rise rate. This precise control helps to achieve the ideal annealing effect, reduce the stress accumulation of the material during the annealing process, and promote crystal orientation. During the annealing process, the gradual decay of the electric field strength helps to reduce the thermal stress accumulation inside the material and reduce the risk of stress cracks generated by the material during the rapid cooling stage, thereby improving the structural integrity and stability of the coating.
[0061] In other embodiments of the present invention, The form can also be: , where A is the linear attenuation coefficient, A is 10 ~1000 V / m s, for example, it can be 10V / m s、100V / m s、1000V / m s. Linear attenuation can provide a stable rate of decrease of electric field strength, making the temperature rise smoothly and linearly, which is conducive to uniform annealing. It is suitable for materials and processes that require a high level of smooth temperature rise. It is easy to control the rate of electric field attenuation and is suitable for annealing in the low to medium temperature range.
[0062] , where B is the coefficient of quadratic attenuation, B is 0.001~0.1 , for example, it can be 0.001 , 0.005 , 0.1 This secondary attenuation mode has a slow decrease in the electric field intensity at the beginning and a fast decrease at the end, which helps to quickly increase the temperature at the beginning of annealing and then gradually slow down the temperature increase rate. It is suitable for annealing processes that require a high initial heating rate but need to maintain stable temperature control in the later stage.
[0063] ; Wherein, C represents the total number of stages in which the electric field intensity decreases, and C is 4 to 8, for example, 4, 6, and 8. If you want the electric field intensity to decrease by the same magnitude and duration in each stage, you can choose uniform segmentation. For example, if the annealing time is 1 hour, it can be evenly divided into 4 stages, each lasting 15 minutes. If you need to maintain a high electric field intensity in the early stage and gradually weaken it in the later stage, you can use non-uniform segmentation. For example, the first two stages are long (20 minutes), and the subsequent stages are gradually shortened to 10 minutes.
[0064] Specifically, step S3.4 includes: performing an nth deposition and an nth annealing on the preliminary coating substrate; It is determined whether the exhaust gas content of the reaction chamber is within a preset gas content range, wherein the preset gas content range is calculated based on the amount of coating powder and chemical reaction.
[0065] Specifically, the exhaust gas of the reaction chamber includes at least one of hydrogen chloride, hydrogen fluoride, water vapor, carbon monoxide, and carbon dioxide.
[0066] During the annealing process of tantalum coating, the gas generation depends mainly on the annealing atmosphere and the chemical composition of the coating. During the annealing process, especially when there is water or moisture, hydrogen and oxide reaction may produce water vapor. The reaction equation can be , water vapor evaporates at high temperature and is discharged from the annealing furnace together with other gases.
[0067] If a chlorine-containing atmosphere or a tantalum source is used during the annealing process, hydrogen chloride gas may be released, especially in the hydrogen reduction reaction. The reaction equation can be , Hydrogen chloride gas is a strong acidic gas and is corrosive, requiring a proper gas exhaust system.
[0068] When tantalum fluoride reacts, hydrogen fluoride is released as a byproduct. During the reaction, fluorine gas reacts with a reducing gas (such as hydrogen) to generate hydrogen fluoride gas. The reaction equation can be Hydrogen fluoride gas is a highly corrosive gas that is harmful to the human body and is volatile at high temperatures.
[0069] When the carbon material and the coating material react in a hydrogen atmosphere, carbon monoxide and carbon dioxide are generated. The calculation method of the preset gas content range of the above gases is known to those skilled in the art and will not be repeated here.
[0070] If yes, stop the next deposition and proceed to step S4; If not, the steps of performing an nth deposition and an nth annealing on the preliminary coating substrate are performed.
[0071] In the above reaction process, the implementation time of each deposition and annealing step can be 0.1-1 h, for example, 0.1 h, 0.5 h, or 1 h.
[0072] In some embodiments of the present invention, the gas detection means are as follows: A mass flow meter can be used to accurately control and monitor the gas flow in real time. By measuring the flow of the reaction gas, the consumption of the deposition material can be indirectly calculated. By using spectral analysis methods such as Fourier transform infrared spectroscopy (FTIR) or ultraviolet visible spectroscopy (UV-Vis), the concentration change of the reaction gas can be monitored in real time to determine the consumption. A gas mass sensor (GMS) can be used to monitor the consumption of the reaction gas during the deposition process online.
[0073] The above sensors and devices can be loaded into the recovery system, and the remaining part of the reaction gas can be recovered through the recovery system, and the concentration analysis can be performed to determine the consumption of the material. The specific structure of the recovery system, sensor and detection device is known to those skilled in the art and will not be described in detail here.
[0074] During the reaction process of forming tantalum carbide, a tracer gas or reaction indicator can be added so that the generated gas can not only change when the coating deposition is completed, but also can be easily detected to help monitor the progress of the reaction and determine whether the deposition process is complete.
[0075] For example, using sulfur-containing compounds as tracers, hydrogen sulfide or sulfur dioxide can be introduced. Trace amounts of sulfur-containing compounds such as hydrogen sulfide or sulfur dioxide can be introduced during the tantalum carbide deposition process. The sulfur may react weakly with the tantalum or carbon during the deposition process, or react with residual surface gases after the deposition is completed to form different sulfides. Both hydrogen sulfide and sulfur dioxide can be easily detected by gas sensors or gas chromatographs (GC). As the deposition approaches completion, the sulfur consumption or gas generation rate may change, thus serving as an indication of the completion of the deposition process.
[0076] Alternatively, using hydrogen chloride, a small amount of sodium chloride or hydrogen chloride source can be added to the reaction atmosphere during the deposition of tantalum carbide. Hydrogen chloride gas reacts with tantalum source or carbon source at high temperature to produce tantalum chloride intermediates or some reaction byproducts. These chlorine-containing gases will disappear or produce stable concentration changes after the deposition is completed. Hydrogen chloride gas can be monitored in real time by a simple chlorine sensor or infrared spectrometer (FTIR). When the reaction is close to completion, the concentration of hydrogen chloride will gradually decrease or reach a state of equilibrium.
[0077] Alternatively, ammonia can be introduced to detect the completion of deposition. Ammonia can be used as a tracer in the reaction atmosphere. During the deposition of tantalum carbide, ammonia may react chemically with certain byproducts or residual carbon surfaces. As the reaction approaches completion, the free activity of the deposition surface gradually decreases and the consumption of ammonia decreases, indicating that the deposition process is approaching completion. Ammonia can be detected by a simple ammonia sensor or monitored in real time using a gas chromatograph (GC) or Fourier transform infrared spectroscopy (FTIR).
[0078] Alternatively, you can choose an indicator with fluorescence or color change. Some compounds will produce fluorescence or color change after reacting with a specific surface. For example, you can choose a gas containing certain metal complexes that will change color when the deposition surface reaches a certain coverage. You can use optical detection methods, such as fluorescence detectors or spectrophotometers, to detect the color change of the deposition surface in real time to determine whether the deposition process is complete.
[0079] For example, molybdate and tungstate complexes, which can be ammonium molybdate and ammonium tungstate, will produce color changes under certain circumstances. For example, in an acidic environment or after high temperature annealing, they will appear blue or yellow, which can be used to indicate the deposition coverage. Use a spectrophotometer to detect the color change of the deposited layer; the color change can indicate the progress of the deposition.
[0080] It can also be a vanadium complex, such as vanadium pentoxide or ammonium metavanadate, which changes from yellow to blue or green when exposed to a reducing atmosphere (such as hydrogen). This color change can be used to detect the uniformity of the deposited layer or whether the expected coverage is achieved. The color change is monitored by a spectrophotometer to observe the color change of the surface during the deposition process.
[0081] It can also be a chromium complex, such as potassium dichromate and potassium chromate. Chromates and dichromates change color significantly in acidic and alkaline environments, showing orange and yellow respectively. When deposited on the surface, a slight change in pH will trigger a color change, which can be used as an indicator of coverage. The color change of the deposited layer can be monitored by a fluorescence detector to judge the progress of the deposition process.
[0082] It can also be a complex of iridium and platinum, such as tris(2-phenylpyridine)iridium and platinum acetylacetonate. These complexes can produce obvious fluorescence under ultraviolet light irradiation. When a certain coverage is reached or when it reacts with the surface of the deposited layer, the fluorescence intensity will change. Iridium complexes and platinum complexes are often used for deposition detection of organic electronic devices. The change of fluorescence intensity is monitored in real time by a fluorescence detector to judge the uniformity and coverage of the deposited layer.
[0083] It can also be a lanthanide complex (such as a complex of europium and terbium), such as tris(trifluoroacetylacetonate) europium (III) and tris(trifluoroacetylacetonate) terbium (III). The europium and terbium complexes emit red and green fluorescence under ultraviolet light, and the fluorescence intensity and emission wavelength are sensitive to the surface conditions of the deposited layer. When the complex is chemically or physically adsorbed to the deposited surface, the fluorescence intensity will change. Use a fluorescence detector or a spectrophotometer to monitor the change in fluorescence intensity, and judge the uniformity and integrity of the deposited layer based on the intensity of the fluorescence.
[0084] It can also be a copper ammonia complex, such as tetraammine copper (II) ion, which is dark blue, and the color change is sensitive to pH and the state of the deposition surface. When the deposition surface reaches a certain coverage, the color change may be caused by adsorption or reaction. The color change can be detected by a spectrophotometer to determine whether the deposition surface has reached the required coverage.
[0085] The introduced tracer gas or reaction indicator can also be used to determine whether it is within the preset tracer gas or reaction indicator range. The preset tracer gas or reaction indicator range is calculated through detailed reactions, which is similar to the exhaust gas and will not be repeated here.
[0086] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a composite substrate for semiconductor device production, characterized in that the steps include: S1. Place the raw carbon into a reaction chamber in a hydrogen atmosphere, evacuate the reaction chamber, heat it to 1000-1500°C, keep it warm for 1-3 hours, and cool and clean it to obtain a carbon substrate; S2, grinding and mixing the tantalum source, tantalum fluoride and flux to obtain coating powder; S3, transferring the coating powder to a reaction chamber with a pulsed electric field, performing pulsed electric field assisted vapor deposition, and obtaining a tantalum carbide pre-coating material with crystal orientation after cooling; S4. Transfer the tantalum carbide pre-coating material to a high-temperature sintering furnace, and heat it at 1800-2400° C. in an inert atmosphere for 0.5-6 hours to obtain a composite substrate, which is used for semiconductor device production.
2. The method for preparing a composite substrate for semiconductor device production according to claim 1, characterized in that: In step S2, the flux includes at least one of sodium fluoride, potassium fluoride, calcium fluoride, sodium chloride, potassium carbonate, sodium carbonate, sodium metaborate, sodium borate, magnesium chloride, calcium chloride, lithium chloride, calcium oxide, and magnesium oxide; The tantalum source includes at least one of tantalum alkane, tantalum vinyl compound, tantalum acetate, and tantalum olefinic compound.
3. The method for preparing a composite substrate for semiconductor device production according to claim 2, characterized in that: Calculated by weight percentage, the tantalum source accounts for 60-80 wt%, the tantalum fluoride accounts for 10-20 wt%, and the flux accounts for 10-20 wt%.
4. The method for preparing a composite substrate for semiconductor device production according to claim 1, characterized in that: The step S3 comprises: S3.1, transferring the coating powder into a reaction chamber with a pulsed electric field and placing the carbon substrate on the interface of the coating powder; S3.2, introducing an inert atmosphere into the reaction chamber and applying a pulsed electric field to perform a first deposition to obtain a preliminary deposition substrate, wherein the deposition temperature of the first deposition is ; S3.3, introducing hydrogen atmosphere into the reaction chamber and adjusting the pulse electric field, performing a first annealing treatment on the preliminary coating substrate to obtain a preliminary coating substrate, wherein the first annealing temperature is ; S3.4, performing an nth deposition and an nth annealing on the preliminary coating substrate to obtain a tantalum carbide pre-coating material, wherein the nth deposition temperature is , the nth annealing temperature is .
5. The method for preparing a composite substrate for semiconductor device production according to claim 4, characterized in that: Said is 800~1000℃, for Said is the rate of change of deposition temperature, is 100~300℃, for , is the rate of change of annealing temperature, It is 200~400℃.
6. The method for preparing a composite substrate for semiconductor device production according to claim 4 or 5, characterized in that: In step S3.3, the formula for adjusting the pulse electric field is: , where t is the upper limit of the integral, indicating the total duration of the annealing process, is the variable in the integration process, representing the time point from the start of annealing to a certain moment, E(t) is the relationship between the pulse electric field intensity and time during the annealing process, is the proportionality coefficient between the temperature increment and the electric field strength, indicating the incremental effect of the electric field strength on the annealing temperature. is the rate at which the pulse electric field affects the temperature, It is the feedback coefficient of the attenuation of the pulse electric field effect during the temperature and annealing process.
7. The method for preparing a composite substrate for semiconductor device production according to claim 6, characterized in that: ,in, is the initial electric field strength, is the attenuation coefficient, which represents the rate at which the pulse electric field intensity decays with time.
8. The method for preparing a composite substrate for producing a semiconductor device according to claim 4, characterized in that: The step S3.4 comprises: Performing an nth deposition and an nth annealing on the preliminary coating substrate; Determining whether the exhaust gas content of the reaction chamber is within a preset gas content range, wherein the preset gas content range is calculated based on the amount of the coating powder and the chemical reaction; If yes, then stop the next deposition and proceed to step S4; If not, the steps of performing the nth deposition and nth annealing on the preliminary coating substrate are performed.
9. The method for preparing a composite substrate for semiconductor device production according to claim 8, characterized in that: The exhaust gas of the reaction chamber includes at least one of hydrogen chloride, hydrogen fluoride, water vapor, carbon monoxide and carbon dioxide.
Citation Information
Patent Citations
Method for preparing refractory metal carbide coating on surface of carbon-based material
CN113149713A
Preparation method of two-dimensional transition metal chalcogenide single crystal oriented growth wafer-level single crystal based on electric field environment
CN116446034A
Semiconductor grown tantalum carbide coated graphite component and method of making same
CN117185838A
Tantalum carbide coated graphite component and preparation method thereof
CN118290180A
Forming method of highly oriented diamond thin film
JP1994321688A
Cited By
TaC / graphite composite material and preparation method thereof
CN120664906A